Linear and Nonlinear Viscoelastic Modulus of Rubber - T. V. Tolpekina; W. Pyckhout-Hintzen; B.N.J. Persson (Lubricants, 2019)
We study the linear and nonlinear viscoelastic properties of two tire tread compounds. We discuss the difference in nonlinear response between the oscillatory tensile and shear modes. We also analyze strain relaxation (creep) data for the same systems. We discuss what type of measurements are most suitable for obtaining the viscoelastic modulus used in rubber friction calculations.